Phytochemical and bioactivity studies of zingiber amaricans blume. - S., Riyanto; Md.Sukari, Mohd. Aspollah; Rahmani, Mawardi; A.M, Ali; N. , Shaharudin (International Congress of Environment, Chemistry and Biology, 2011)
Phytochemical studies on the rhizomes of Zingiber amaricans afforded zerumbone1 as the major constituent, together with sterol mixtures containing, stigmasterol2, β-sitosterol3, cholesterol4 and campesterol5. The structures of the isolated compounds were elucidated using spectroscopic methods. The crude extracts and isolated pure compounds were examined for their bioactivity against phatogenic microbes and cancer cell lines. Zerumbone1 shows moderate cytotoxic activity against human lymphoblastic T leukemia cell.